A Study on Adherence to International Patient Safety Goals in a Tertiary Care Cardiac Centre in India (Medico Legal Update, 2019)
Introduction: Aim:To assess adherence to International Patient Safety Goals among medical and paramedicalstaff.Objectives:To assess awareness levels about the goals amongst the hospital staff and implementation ofthe goals by the medical and paramedical staff.Method: This is a cross-sectional study.The stratified sampling method was used where the healthcareproviders who are directly associated with patients in patient care,were sub-grouped into doctors, nurses andparamedical staff which include physiotherapists,lab technicians,radiologists, dieticians,etc. 18% - 20% ofthe staff under each sub-group was randomly considered for sampling.A structured observational checklistwas used along with interview and the questionnaire consisted of 20 questions covering all the 6 goals.Thestudy was carried out from 3rd May 2017 to 15th June 2017 with a sample size of 306 in total.Results and Discussion: Overall compliance (category wise) is observed to be highest in Doctors with 72%,followed by Nurses with 69% and then Paramedics with 68% compliance.It was noted that the cause of non-compliance with the goals by staff was either because of lack of knowledgeor extra work load which reduces the ease of implementation or sometimes combination of both.Doctors andparamedical staff have mentioned insufficient training classes as the reason for their non-compliance.Nurseshad classes on a regular basis but still failed to acknowledge and implement the same.